Single crystal growth of Ni-base superalloys by the conventional vertical bridgman and novel submerged baffle methods - Bacak, Mert. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
The purpose of this study is to develop a know-how on the growth of single crystal superalloys and investigate the e ect of solidi cation rate and solidi cation technique on microstructural features of CMSX-4. Primary dendrite arm spacing (PDAS), dendrite core size, mushy zone length, melt-back transition length, porosity and microsegregation are investigated by comparing two di erent solidi cation techniques: the Vertical Bridgman (VB) technique and the Vertical Bridgman with a Submerged Ba e (VBSB) technique. The VBSB technique employs a ceramic disk (ba e) immersed in the melt. The melt is separated into two zones. The small zone below the ba e reduces the melt height, leading to a reduction convection. Samples produced by the VBSB technique show higher PDAs and dendrite core size than those produced by the VB technique. This e ect is attributed to decreased convection. Along the height of all samples, PDAS and dendrite core size exhibit an increase. This is due to a decreasing thermal gradient at the s/l interface away from chill plate. Mushy zone and melt-back lengths are decreased for the samples grown with VBSB technique. This can be explained by the higher thermal gradients due to diminished convection. Samples produced by the VBSB technique show lower porosity than those produced by the VB technique, and the e ect is more pronounced than for the mushy zone permeability and length. Overall the results show that the amount of convection has a considerable e ect on the microstructure of directionally solidi ed superalloys. Moreover, the Vertical Bridgman with a Submerged Ba e technique can decrease the convection by decreasing the melt height above the solidi cation interface.
Keywords: Crystal growth.